2009
DOI: 10.1007/s10681-009-9937-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of gene-tagged markers for quantitative trait loci underlying rice yield components

Abstract: Higher yields of rice have always been a predominant goal in rice breeding techniques. However, the inheritances of rice yield and its components are still unknown, and no information regarding suitable alleles can be directly provided for improving the rice yield level until three major quantitative trait loci (QTLs) have been cloned and functionally characterized. These QTLs contain Gn1a for grain number per panicle and GS3 and GW2 for grain weight. It has been proven that these three genes show a potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…Because real‐time measurements of photosynthesis are laborious and easily influenced by environmental changes, they are not generally appropriate for genetic analysis. We have established some rapid and precise methods to indirectly evaluate photosynthesis by measuring related traits (Takai et al, 2006a, 2009, 2010a, 2010b). For example, the SPAD value and LNC, which reflect chlorophyll content and the amount of the ribulose‐1,5‐bisphosphate carboxylase oxygenase (Rubisco) protein, can be easily measured using a SPAD meter and a N and C analyzer, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because real‐time measurements of photosynthesis are laborious and easily influenced by environmental changes, they are not generally appropriate for genetic analysis. We have established some rapid and precise methods to indirectly evaluate photosynthesis by measuring related traits (Takai et al, 2006a, 2009, 2010a, 2010b). For example, the SPAD value and LNC, which reflect chlorophyll content and the amount of the ribulose‐1,5‐bisphosphate carboxylase oxygenase (Rubisco) protein, can be easily measured using a SPAD meter and a N and C analyzer, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Koshihikari is a leading japonica variety in Japan (Yamamoto et al, 2010), but its yields are relatively low compared to indica and indica – japonica varieties or something similar. Takanari is one of the highest yielding japonica – indica varieties in Japan (Imbe et al, 2004) with a greater photosynthetic rate in the flag leaves at the heading stage than Koshihikari (Ohsumi et al, 2007; Takai et al, 2010b). Tongil is a high‐yielding indica variety grown in Korea (Chung and Heu, 1980).…”
Section: Methodsmentioning
confidence: 99%
“…Because of this, the studies on rice photosynthesis are only focused on rice blade up to now [12]. However, in this study, we found that rice sheath was also rich in photosynthetic cells in its outer epidermis ( Fig.…”
Section: Discussionmentioning
confidence: 62%
“…To solve this problem, attention has been paid in recent years to the photosynthesis of high-yielding rice varieties [2][3]. The different aspects of the photosynthesis in high-yielding rice varieties have been studied by many researchers, such as high photosynthetic efficiency [4][5], efficiency of solar energy utilization [6], distribution of assimilates [7], leaf senescence [8], environmental stresses [9], ideal plant type of super hybrid rice [10][11], stomata [7], genetic expression [12], and so on. Heterosis of rice was used in China and new high photosynthetic rice varieties such as super hybrid rice were cultured, which showed the morphological features including its long, narrow, and erect top leaves [10,13], which is characterized as ideal plant type rice [13] and this type of rice is reported to trap more solar energy [3,10].…”
Section: Introductionmentioning
confidence: 99%
“…GS3 is a major QTL for grain length and grain weight and a minor QTL for grain width (Fan et al 2006). Yan et al (2009) and Xu et al (2015b) have developed markers for the functional site or tightly linked sites of GS3. qGL3 is a major QTL for grain length, encoding a putative protein phosphatase with Kelch-like repeat domain (OsPPKL1) (Zhang et al 2012).…”
Section: Qtls For Grain Shape and Grain Weight Traitsmentioning
confidence: 99%